2017
DOI: 10.1111/jsbm.12366
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Graduates' Start-Ups Creation across a Multi-Campus Entrepreneurial University: The Case of Monterrey Institute of Technology and Higher Education

Abstract: Individual and organizational entrepreneurial activity varies across regions/countries. Universities have increasingly become knowledge‐intensive environments that support entrepreneurship. Extant studies demonstrate the need to explore graduate start‐ups using different levels of analysis an across economies. This paper explores individual and university determinants of graduates' start‐ups creation from a multi‐campus entrepreneurial university in a transition economy. A proposed model was tested with 11,569… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 139 publications
4
80
2
6
Order By: Relevance
“…The special interest in the developments in Tertiary Education that is shown today at the level of regional science is attributed to the research topic focusing on the relationships among universities, knowledge and regional development, which dates back several decades ago. Some main concepts that were used from time to time to enlighten different components and dynamics include the "Triple Helix" for the study of the relationships among Universities-Government and Industry (Etzkowitz and Leydesdorff 2000), the "Learning Region" (Shaw and Allison 1999;Maskell and Tornqvist 2003;Saxenian 1994), the "Quadruple Helix" (Committee of the Region 2014; Park 2014), the "Regional Innovation Systems" (Benneworth et al 2017) and the "Entrepreneurial University" (Audretsch 2014;Guerrero et al , 2017.…”
Section: Locus Of Actionmentioning
confidence: 99%
“…The special interest in the developments in Tertiary Education that is shown today at the level of regional science is attributed to the research topic focusing on the relationships among universities, knowledge and regional development, which dates back several decades ago. Some main concepts that were used from time to time to enlighten different components and dynamics include the "Triple Helix" for the study of the relationships among Universities-Government and Industry (Etzkowitz and Leydesdorff 2000), the "Learning Region" (Shaw and Allison 1999;Maskell and Tornqvist 2003;Saxenian 1994), the "Quadruple Helix" (Committee of the Region 2014; Park 2014), the "Regional Innovation Systems" (Benneworth et al 2017) and the "Entrepreneurial University" (Audretsch 2014;Guerrero et al , 2017.…”
Section: Locus Of Actionmentioning
confidence: 99%
“…So is the case with universities that transform themselves from traditional paradigm into Entrepreneurial University. Several universities currently are transforming into an ecosystem that utilizes knowledge to support entrepreneurship as an effort to create knowledge-based economy (Etkowitz, 2004;Etkowitz, et al, 2008;Guerrero, et al, 2018).…”
Section: Transformation Of Entrepreneurial Universitymentioning
confidence: 99%
“…The research conducted by Cohen, Nelson, and Walsh (2002) and Guerrero andUrbano (2017) (in Guerrero et al, 2018) concluded that there are 2 (two) important roles of universities in promoting entrepreneurship. First, universities have transformed into an environment that intensifies knowledge to support entrepreneurship through significant roles of combination of human resources and aspiration in the number of start-ups made by their graduates.…”
Section: Transformation Of Entrepreneurial Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies have focused on for example the use of technology transfer offices (Muscio 2010), cultural differences (Lin and Berg 2001); institutional dimensions of R&D collaborations (Bjerregaard 2010), motivations (Cunningham et al 2016a;D'este and Perkmann 2011;Hayter 2017), communications (Barnes et al 2002;Plewa et al 2013), time allocations (Ponomariov and Boardman 2008) and barriers to university collaboration Hall et al 2001;O'Reilly and Cunningham 2017;O'Kane et al 2017). Over the last decade there have been a growing micro level focus on better understanding technology transfer through the experiences of individual actors involved in the technology transfer process such as academic entrepreneurs 1 3 (Bercovitz and Feldman 2008;Mosey and Wright 2007;Miller et al 2017) scientists (Link et al 2007) star scientists (Baba et al 2009;Meyer 2006), principal investigators (Cunningham et al 2016a;Cunningham et al 2017a;Cunningham et al 2018;Del Giudice et al 2017;Menter 2016), technology entrepreneurs and graduate students (see Evers et al 2014;Guerrero et al 2018;Hayter et al 2017;RezaeiZadeh et al 2017;Watson and McGowan 2017;Watson et al 2018).…”
Section: Introductionmentioning
confidence: 99%